THE EFFECT OF EDIBLE COATING FROM CARRAGEENAN ON THE QUALITY OF FRESH FEMALE MACKEREL (Rastrelliger brachysoma) DURING COLD TEMPERATURE STORAGE - Slamet Nur Arifin; N Ira Sari; Suparmi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research aims to determine the effect of edible coating is made of carrageenan on the quality of fresh female mackerel during cold storage temperatures. The research was conducted in August 2014 which took place at the Laboratory of Fishery Technology, Fishery Products Chemistry, Laboratory of Microbiology and Biotechnology of Fishery Faculty of Fisheries and Marine Sciences, University of Riau. The experimental design used was a randomized block design (RBD) one factor with treatment K0 (without carrageenan), K1 (carrageenan 1 g), K2 (carrageenan 2 g), K3 (carrageenan 3 g) and K4 (carrageenan 4 g), long storage (group) is 0, 1, 2, 3, 4 weeks. Quality parameters are observed organoleptic test, TVB and pH. Research results carrageenan edible coating made with the best treatmentis the treatmen K2 (carrageenan 2g) seen from the results of organoleptic value with the average value of the eye(6.64), the body surface mucus(6,60), the meat/color (6,48), smell (7.36), texture (6.56), the value of TVB (32 mgN/100g) and pH value (7.05).Keywords: edible coating, carrageenan, female mackerel.